Analysis of magnetic field effect on ferromagnetic spheres embedded in elastomer pattern. - Boczkowska, Anna; Czechowski, Leszek; Jaroniek, Mieczysław; Niezgoda, Tadeusz (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2010)
The results of modelling of the magnetorheological elastomers (MREs) microstructure using Finite Elements Method (FEM) are shown. MREs are solids analogous to magnetorheological fluids consisting of carbonyl-iron particles and a soft elastomer matrix. Fabrication of MREs is performed in an external constant magnetic field. Due to the presence of this field, the ferromagnetic particles tend to arrange themselves into elongated chains according to the magnetic field lines. FEM analysis of the MREs microstructure takes into account two cases: magnetic power and elastic vectors as well as their interactions between the components of the composite. The paper describes spatial ordering of the particles based on their interactions with the magnetic field. Two phenomena were taken into account: the force of a magnetic field and the local magnetic dipoles. Both fields have been modelled for a circular conductor with electrical current.

W pracy przedstawiono wyniki modelowania mikrostruktury magnetoreologicznych elastomerów (MRE) z wykorzystaniem metody elementów skończonych (MES). MRE są odpowiednikami w stanie stałym cieczy magnetoreologicznych, złożonymi z cząstek żelaza karbonylkowego i miękkiej osnowy elastomerowej.Wytwarzanie MRE prowadzone jest w stałym polu magnetycznym. Pod wpływem pola cząstki ferromagnetyczne układają się w łańcuchy wzdłuż linii pola magnetycznego, tworząc strukturę kolumnową. W analizie MES mikrostruktury MRE rozpatrzono siły magnetyczne i sprężystości oraz ich wzajemne oddziaływania pomiędzy składnikami kompozytu. Przedstawiono przestrzenne rozmieszczenie cząstek w oparciu o ich oddziaływania w polu magnetycznym. W rozważaniach wzięto pod uwagę rozkład pola magnetycznego i momenty dipolowe cząstek. W obu przypadkach pole było zamodelowane dla kołowego przewodnika prądu elektrycznego.
Badanie wpływu pola magnetycznego na ferromagnetyczne kule w osnowie elastomerowej.
Keywords: magnetorheological elastomers; Finite Element Method; photoelastic method; magnetoreologiczne elastomery; metody elementów skończonych; pole magnetyczne; ferromagnetyczne kule; osnowa elastomerowa